Internalization of Muscle-Specific Kinase Is Increased by Agrin and Independent of Kinase-Activity, Lrp4 and Dynamin - Gemza, Anna; Barresi, Cinzia; Proemer, Jakob; Hatami, Jasmin; Lazaridis, Margarita; Herbst, Ruth (Frontiers in Molecular Neuroscience, 2022)
Muscle-specific kinase (MuSK) is a receptor tyrosine kinase absolutely required for neuromuscular junction formation. MuSK is activated by binding of motor neuron-derived Agrin to low-density lipoprotein receptor related protein 4 (Lrp4), which forms a complex with MuSK. MuSK activation and downstream signaling are critical events during the development of the neuromuscular junction. Receptor tyrosine kinases are commonly internalized upon ligand binding and crosstalk between endocytosis and signaling has been implicated. To extend our knowledge about endocytosis of synaptic proteins and its role during postsynaptic differentiation at the neuromuscular junction, we studied the stability and internalization of Lrp4, MuSK and acetylcholine receptors (AChRs) in response to Agrin. We provide evidence that MuSK but not Lrp4 internalization is increased by Agrin stimulation. MuSK kinase-activity is not sufficient to induce MuSK internalization and the absence of Lrp4 has no effect on MuSK endocytosis. Moreover, MuSK internalization and signaling are unaffected by the inhibition of Dynamin suggesting that MuSK endocytosis uses a non-conventional pathway and is not required for MuSK-dependent downstream signaling.